PHARMACEUTICAL FORMS BASED ON CHELIDONIUM MAJUS L - Olimpia Dumitriu Buzia; Ion Gianina Mihaela; Earar Kamel; Tiutiuca Carmen; Batir Marin Denisa; Zetu Irina; Debita Mihaela; Stoian Valerian Ionut; Mardare Nela (Romanian Journal of Oral Rehabilitation, 2022)
Given the abundant amount of hollyhock in the environment, given the special propertiesof the plant, used both internally, in hepato-biliary disorders and externally in various dermatological diseases, we set out to achieve a physical-chemicaland technological study. of this plant